Phosphate-sensing with (di-(2-picolyl)amino)quinazolines based on a fluorescence on–off system. Issue 26 (17th April 2020) - Aoki, Kazusa; Osako, Ryuji; Deng, Jiahui; Hayashita, Takashi; Hashimoto, Takeshi; Suzuki, Yumiko
Abstract : Supramolecular probe Cu-dpa-QZ2 /FPB-γ-CyD recognized ATP with high sensitivity. Abstract : Detection and visualization of phosphates such as ATP in living organisms can facilitate the elucidation of various biological events. Although substantial efforts had been made in this area, present methods have disadvantages such as the need for specialized equipment and poor sensitivities. To address these limitations, novel fluorescent probes, (di-(2-picolyl)amino)quinazolines, were developed for application in ATP detection. They selectively recognized copper ions by fluorescence quenching, and their copper complexes displayed fluorescence enhancement in the presence of phosphoric acid derivatives. This fluorescence on–off system enabled highly sensitive fluorescence detection of ATP when combined with a phenyl boronic acid-modified γ-cyclodextrin through a plausible multipoint recognition system.